A novel Glycyrrhiza glabra extract liquiritin targeting NFATc1 activity and ROS levels to counteract ovariectomy-induced osteoporosis and bone loss in murine model - Hong, Guoju; Zhou, Lin; Zheng, Guanqiang; Zheng, Xiaoxia; Chen, Zhenqiu; He, Wei; Wei, Qiushi (Frontiers in Pharmacology, 2023)
Osteoporosis, a prevalent osteolytic condition worldwide, necessitates effective strategies to inhibit excessive bone resorption by curbing osteoclast hyperactivation. Liquiritin (LIQ), an artemisinin derivative employed in acute lung injury and rheumatoid arthritis treatment, possesses an unclear role in addressing excessive bone resorption. In this investigation, we found that LIQ demonstrates the ability to inhibit osteoclast formation and the bone-resorbing activity induced by RANKL. At a specific concentration, LIQ significantly attenuated NF-κB-Luc activity induced by RANKL and curtailed NF-κB activation in RANKL-stimulated RAW264.7 cells, resulting in reduced IκB-α breakdown and diminished nuclear NF-κB levels. Furthermore, LIQ markedly inhibited RANKL-induced NFATc1 activation, as evidenced by diminished NFAT luciferase activity, reduced NFATc1 mRNA levels, and decreased nuclear NFATc1 protein levels. Subsequent experiments demonstrated that LIQ effectively restrained the RANKL-induced elevation of intracellular calcium as well as reactive oxygen species. Additionally, LIQ exhibited a downregulating effect on the expression of osteoclast-specific genes, which include Acp5, Cathepsin K, Atp6v0d2, Nfatc1, c-Fos, and Mmp9. Notably, our findings revealed the potential of LIQ to counteract decreased bone density in mice that un-derwent ovariectomy. Collectively, the data indicate that LIQ impedes osteoclast formation triggered by RANKL and the subsequent reduction in bone mass by mitigating ROS levels and suppressing the Ca2+/MAPK-NFATc1 signaling pathway, suggesting its promising candidacy as a therapeutic agent for RANKL-mediated osteoporosis.